The Monkey King’s Somersault - Chen, Yannic (Journal of Interdisciplinary Science Topics, 2017)
The Monkey King is a famous fictional character from ancient Chinese literature. A famous saying is that he can travel a distance of 54,000km on a somersault. Such a distance requires a jump height of 13,500km. This feat is inefficient on the Earth, which has dimensions smaller than the jump and as a result, may only be helpful in the Heavenly Kingdom with unknown properties and parameters.